THE USE OF WEIGHTENING IN SPEED-POWER TRAINING OF ATHLETES IN CLIMBING - Балухтина, Валентина; Зюзь, Володимир (SWorldJournal, 2022)
Climbing competitions are currently held on artificial terrain. Changes in the structure of climbing entailed a change in the arsenal of techniques, the direction of physical development of athletes and training methods. There are many reasons for the